Switch, disperse, repeat: host specificity is highly flexible in rodent-associated Eimeria. Issue 11 (October 2021) - Trefancová, Aneta; Kvičerová, Jana; Mácová, Anna; Stanko, Michal; Hofmannová, Lada; Hypša, Václav
Graphical abstract: Highlights: Eimeria of 2 ecologically similar rodent groups form a complex system of genetic lineages with different host specificities. The lineages retained their host specificities while spreading across large geographic areas. The genetic structure is only partially reflected by morphological traits. Abstract: Interplay between conserved host specificity and occasional host switches is an important process determining the evolution of host-parasite systems. Here, we address the dynamics of host switches at the population level in rodent-associated Eimeria . Focusing mainly on two ecologically similar host groups, Murinae and Arvicolinae, we show that the Eimeria infecting those hosts form a complex system of many genetic lineages with different host specificities. The broad geographic distribution of lineages indicates that they are well-established genetic forms which retained their host specificities while spreading across large geographic areas. We also demonstrate that genetic structure is only partially reflected by morphological traits.